Generalized moment representations and invariance properties of Padé approximants - Holub, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
By the method of generalized moment representations, we generalize the well-known invariance properties of Padé approximants under linear-fractional transformations of approximated functions.